Incentives of stock option based compensation - Elettra Agliardi; Rainer Andergassen (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
We introduce explicitly the effort as a choice variable in a continuous time utility maximisation framework of an executive who is partly compensated with stock options. We solve the model in the case where the executive is not allowed to trade in the company's stock but is able to achieve a partial insurance through trading in a correlated market portfolio. We define the executive's value of the options through a certainty equivalence approach both in the case of European call options and nonstandard capped stock options and study the behaviour of the reservation price as relevant parameters change.
Keywords: 330